Review on V. V. Spivak's monography "Philosophical views by Antony Radivilovsky in the context of the Ukrainian spiritual culture of the XVII century"(Chernigiv: Scriptorium, 2018, 328 p.) - V. G. Napadysta, (Ukrainian Cultural Studies, 2019)
The 17th century in the intellectual history of Ukraine, rich in a whole constellation of outstanding church thinkers (Petro Mohyla, Innokenty Gisel, Lazar Baranovych, Ioanikyi Galyatovskyi), is not deprived of the attention of modern scientists, whose creative searches culminated in fundamental research of historical, literary and philosophical direction.